2016
DOI: 10.3928/00904481-20160411-01
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention for Medically Refractory Hyperthyroidism

Abstract: Pediatric hyperthyroidism can be multifactorial, with Graves' disease (GD) being the most common etiology. Treatment focuses on identification of the cause of the hyperthyroidism and achieving a biochemical cure with symptom resolution. This article highlights the clinical presentation, diagnosis, and treatment of a pediatric patient with GD. [Pediatr Ann. 2016;45(5):e171-e175.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…As a first-line treatment for patients with GD, MMI, a representative drug of ATD, can not only alleviate clinical symptoms of GD but also significantly improve thyroid function. However, there was still evidence of relapse in patients with GD after ATD withdrawal ( 11 13 , 21 ) and during drug reduction ( 17 20 ). Previous studies mainly considered age (<40 years), gender, smoking history, FT3/FT4 ratio at withdrawal, goiter degree, TRAb titer, TSH level (at withdrawal) and duration of treatment were closely associated with relapse after ATD withdrawal ( 2 , 13 , 22 24 ), while there were barely evidence suggested that relapse risk factors during drug reduction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a first-line treatment for patients with GD, MMI, a representative drug of ATD, can not only alleviate clinical symptoms of GD but also significantly improve thyroid function. However, there was still evidence of relapse in patients with GD after ATD withdrawal ( 11 13 , 21 ) and during drug reduction ( 17 20 ). Previous studies mainly considered age (<40 years), gender, smoking history, FT3/FT4 ratio at withdrawal, goiter degree, TRAb titer, TSH level (at withdrawal) and duration of treatment were closely associated with relapse after ATD withdrawal ( 2 , 13 , 22 24 ), while there were barely evidence suggested that relapse risk factors during drug reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Enrolled GD patients were divided into two groups: Drug reduction relapse group ( n = 88): During ATD treatment, patients with GD were cured or the clinical symptoms were relieved. While after FT3, FT4, and TSH returned to normal levels, the situation of increased FT3 and FT4 appeared again ( 17 20 ). Drug reduction remission group ( n = 137): During ATD treatment, the clinical symptoms were relieved, and FT3, FT4, and TSH returned to normal levels ( 18 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations